Author Citation Award - Zopiatis, Anastasios (My University, 2026)
International Conference on Interdisciplinary Research in Higher Education (ICIRHE 2017), 28th – 30th of June, 2017, Siem Reap, Cambodia. Recipient of the Author Citation Award
Keywords: Business and industry